2018
DOI: 10.1103/physrevlett.120.097001
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic Order in Epitaxial FeSe Films on SrTiO3

Abstract: Single monolayer FeSe film grown on a Nb-doped SrTiO_{3}(001) substrate shows the highest superconducting transition temperature (T_{C}∼100  K) among the iron-based superconductors (iron pnictides), while the T_{C} value of bulk FeSe is only ∼8  K. Although bulk FeSe does not show antiferromagnetic order, calculations suggest that the parent FeSe/SrTiO_{3} films are antiferromagnetic. Experimentally, because of a lack of a direct probe, the magnetic state of FeSe/SrTiO_{3} films remains mysterious. Here, we re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 60 publications
4
24
0
Order By: Relevance
“…The suppressed low-energy excitation and tendency for a magnetic order rather result from the local two-particle vertex, which includes effects of overall increase of local orbital occupations away from the integer filling by doping, which should suppress the fluctuating moment and enhance charge fluctuations. Zero ordered moment is obtained in the stripe-type AFM calculation for 0.12 e − /Fe doped ML FeSe, in consistence with our χ 00 m result in the PM phase and also with the suppressed magnetic order by electron doping found experimentally 35 as mentioned above. This large sensitivity of magnetic order on doping therefore results from local correlations, which are well described within the DFT + DMFT method.…”
Section: Effects Of Doping On ML Fesesupporting
confidence: 87%
See 1 more Smart Citation
“…The suppressed low-energy excitation and tendency for a magnetic order rather result from the local two-particle vertex, which includes effects of overall increase of local orbital occupations away from the integer filling by doping, which should suppress the fluctuating moment and enhance charge fluctuations. Zero ordered moment is obtained in the stripe-type AFM calculation for 0.12 e − /Fe doped ML FeSe, in consistence with our χ 00 m result in the PM phase and also with the suppressed magnetic order by electron doping found experimentally 35 as mentioned above. This large sensitivity of magnetic order on doping therefore results from local correlations, which are well described within the DFT + DMFT method.…”
Section: Effects Of Doping On ML Fesesupporting
confidence: 87%
“…The stabilization of the AFM phase in ML FeSe on SrTiO 3 has been also predicted by previous DFT calculations 29,33,34 , however, with large ordered moments of over 2 μ B , which are likely overestimated as is a well-known general property of DFT on IBS. A recent experimental work indeed confirmed an AFM order in this system using magnetic exchange bias effect measurement 35 , though neither the ordering vector nor the ordered moment could be determined. It is also found that the magnetic order disappears for the electron doped sample where superconductivity can arise.…”
Section: Effects Of Doping On ML Fesementioning
confidence: 78%
“…This prediction is consistent with the recent experimental observation that monolayer FeSe deposited on SrTiO 3 exhibits AFM order. 48…”
Section: Thermodynamic Stabilitymentioning
confidence: 99%
“…However, the checkerboard AFM might develop in the FeSe domain boundaries, since the electronic properties, such as the broken two-fold symmetry and the in-plane lattice expansion, are similar to that in 1 UC FeSe /STO, 6 in which a recent study shows experimental evidence for AFM order. 29 DFT calculations are carried out to study the possible topological origin of the edge states with AFM. For a two-dimensional (2D) film, the topological invariance usually oscillates with the number of layers 30,31 .…”
mentioning
confidence: 99%